Temporal Evolution of Maternal Mortality: 1980-2019 - Janete Vettorazzi; Edimárlei Gonsales Valério; Maria Alexandrina Zanatta; Mariana Hollmann Scheffler; Sergio Hofmeister de Almeida Martins Costa; José Geraldo Lopes Ramos (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2021)
Abstract Objective To determine the profile of maternal deaths occurred in the period between 2000 and 2019 in the Hospital de Clínicas de Porto Alegre (HCPA, in the Portuguese acronym) and to compare it with maternal deaths between 1980 and 1999 in the same institution. Methods Retrospective study that analyzed 2,481 medical records of women between 10 and 49 years old who died between 2000 and 2018. The present study was approved by the Ethics Committee (CAAE 78021417600005327). Results After reviewing 2,481 medical records of women who died in reproductive age, 43 deaths had occurred during pregnancy or in the postpartum period. Of these, 28 were considered maternal deaths. The maternal mortality ratio was 37.6 per 100,000 live births. Regarding causes, 16 deaths (57.1%) were directly associated with pregnancy, 10 (35.1%) were indirectly associated, and 2 (7.1%) were unrelated. The main cause of death was hypertension during pregnancy (31.2%) followed by acute liver steatosis during pregnancy (25%). In the previous study, published in 2003 in the same institution4, the mortality rate was 129 per 100,000 live births, and most deaths were related to direct obstetric causes (62%). The main causes of death in this period were due to hypertensive complications (17.2%), followed by postcesarean infection (16%). Conclusion Compared with data before the decade of 2000, there was an important reduction in maternal deaths due to infectious causes.